2022
DOI: 10.1007/s00521-022-08125-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroevolution gives rise to more focused information transfer compared to backpropagation in recurrent neural networks

Abstract: Artificial neural networks (ANNs) are one of the most promising tools in the quest to develop general artificial intelligence. Their design was inspired by how neurons in natural brains connect and process, the only other substrate to harbor intelligence. Compared to biological brains that are sparsely connected and that form sparsely distributed representations, ANNs instead process information by connecting all nodes of one layer to all nodes of the next. In addition, modern ANNs are trained with backpropaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Information theoretic approaches complement these correlational analysis, and have been used to characterize cognitive and computational systems alike (Tononi, 2004;Marstaller et al, 2013;Tehrani-Saleh & Adami, 2020;Hintze & Adami, 2023), and can also be combined with perturbation analysis (Bohm et al, 2022;Hintze & Adami, 2022).…”
Section: Types Of Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information theoretic approaches complement these correlational analysis, and have been used to characterize cognitive and computational systems alike (Tononi, 2004;Marstaller et al, 2013;Tehrani-Saleh & Adami, 2020;Hintze & Adami, 2023), and can also be combined with perturbation analysis (Bohm et al, 2022;Hintze & Adami, 2022).…”
Section: Types Of Manipulationsmentioning
confidence: 99%
“…This is another place where evolved systems differ from those typically used in AI: real brains tend to be more modular and sparsely connected compared to artificial neural networks (Happel & Murre, 1994). Using evolutionary algorithms that specify the presence or absence of connections rather than just their weight (Hintze et al, 2017;Hintze & Adami, 2022), creating and testing modular systems that perform specific functions (Bryson, 2005;Ellefsen et al, 2015), and drawing on the structure of the brain and biological systems (W. Cox & Dean, 2014) are likely to lead to more effective neural networks as well as artificial systems that more closely resemble the human brain.…”
Section: Types Of Manipulationsmentioning
confidence: 99%
“…Previous research has indicated that representations, or the information a neural network possesses about its environment, are dispersed throughout deep-learned networks [ 23 , 24 , 25 , 26 ]. In contrast, neural networks optimized using genetic algorithms do not exhibit this tendency and demonstrate greater robustness to noise [ 24 , 27 , 28 ]. Likewise, human brains, which have been “optimized” by evolution, employ distinct brain regions for computation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%